ICT-competence of university lecturers: diagnostics and development - O. A. Chuvgunova (Открытое образование (Москва), 2019)
The purpose of the study. This article is devoted to reveal the directions of development of lecturers’ information and communication technology (ICT) competences. The level of lecturers’ ICT-competence, feedback from students about efficiency of ICT using at the University, structure of lecturers’ ICT-competence and communicative competence correlation, lecturers’ demands in ICT-competence training were investigated. Methods. Lecturers’ survey (questionnaire “ICT-using by University lecturers” by O. Chuvgunova), students’ survey (questionnaire “ICT at University: students’ feedback” by O. Chuvgunova), psychological test (“Communicative skills test” by L. Michelson), math statistics methods. Sample was formed from lecturers (N = 102) and students (N = 198) of St. Petersburg University. Results. Results show that lecturers have high marks of base level and technological level of ICT competence. Lecturers have ICT literacy and can use ICT as a tool for communication with students. But professional level of the most part of participants’ ICT competence is not developed well enough. Hence, some lecturers cannot create and implement new instruments, methods into educational process through ICT. The feedback from undergraduates demonstrates that students appreciate highly using ICT at their faculties. Respondents think that ICT improves the effectiveness of learning process. At the same time, it is important for students to take into account their individual characteristics and the optimal balance between virtual and “live” communication. Study revealed positive correlation between indicators of ICT competence and communicative competence. Lecturers with high communicative competence have high level of ICT competence and high self-rating of their own ICT competence. Lecturers are interested in ICT-competence training. Mostly, they use different courses and self-education. Most lecturers do not have a plan of their ICT-competence development. Conclusion. The study found out such directions of lecturers’ ICT-competence development, as:– using ICT as a resource of improvement of educational process, development of students’ intelligence and creativity; – lecturers should take into account students’ individual features and students’ feedback through ICT using; – enhancement of lecturers’ communicative competence as a necessary skill of interactive ICT using; – efficiency increase of lecturers’ ICT competence training through permanent educational environment and consulting by ICT specialists.